Effect of metal oxide nanoparticle on curing kinetic of bioresin - Wan Nurul Najihah, Wan Ghafar (2015)
Development of polymers from renewable resources have received great scientific attention. Amongst different renewable resources, plant oils have attracted much attention as raw materials for chemical industry. Vegetable oils have been utilized in the synthesis of various polymeric resin such as alkyd resins and polyester. Alkyd resins find an extensive applications in surface-coating, adhesive and composite materials. Alkyd resins were blended with other suitable resins to overcome problems such as low mechanical strength, low hardness, low thermal stability, and long curing time. Polymer nanocomposite based on nanoparticles such as metal oxide are being developed. Nanoparticles are reported to have strong impact on thermal, mechanical, electrical barrier, and flame retardant properties on nanocomposite. In the present study, alkyd resin was prepared from the vegetable oil (ratio of Palm oil to Jatropha oil at 1:1) via two stage method (alcoholysis-polyesterification). The alkyd resin was mixed with commercial epoxy resin to form a blend mixture. Apart from that, zinc oxide (ZnO) nanoparticle was mechanically mixed with the blend to form alkyd-epoxy-ZnO. Prior to that, ZnO was synthesized using a simple precipitation method. The as-prepared ZnO was characterized by X-ray diffraction (XRD) and the crystallite size was calculated by using Debye-Scherrer’s equation. Scanning electron microscopy (SEM) was used to characterize the morphologies of the sample. The curing kinetic of alkyd-epoxy-ZnO blend was investigated by using non-isothermal differential scanning calorimetry (DSC) method. The effect of alkyd/epoxy ratio and ZnO nanoparticle loading on curing enthalpy was investigated. From DSC results, the peak temperature, Tp is used to calculate the activation energy, Ea by using Kissinger and Ozawa method. In addition, thermogravimetric analysis (TGA) was carried out to study the thermal degradation of the nanocomposites. The interaction between ZnO nanoparticles and the alkyd/epoxy blend were recorded by Fourier-transform infrared (FTIR). All the results from the analysis deduce a conclusion that the ZnO nanoparticles have significant effects on the performance characteristics of alkyd/epoxy blends.